Fear of Missing Out and Perceived Quality Effect on Purchase Intention by Students - Andrew, Richard; Suryawan, Ian Nurpatria; Kusumahadi, Rafaela Abigail (Forum Kerjasama Pendidikan Tinggi, 2023)
In this modern business world, plenty of people in the society had the tendency for having Fear of Missing Out (FOMO) symptoms. This tendency is getting worsed when the person perceived his or herself lack of quality and had the tendency of rejected by the society. These two kind of problems usually blocked someone to buy a product they needed. It is hypothetically appear not only in the business world but sometimes the symptoms already appear in the education fields. As researchers from different background, anticipation of these problems is needed. Because of that, the main objective of this research is determining the effect of FOMO and perceived quality to purchase intention. The research will took 66 samples from students across various program in the university and using the Statistical Product and Service Solutions (SPSS) for interpreting the regression model output. The research concluded that FOMO and perceived quality have significant influence to students’ purchase intention.